Penile skin tube flap salvage urethroplasty for bulbar urethral necrosis following anastomotic urethroplasty for pelvic fracture urethral injury - Yoshiyuki Furukawa; Akio Horiguchi; Masayuki Shinchi; Kenichiro Ojima; Yusuke Hirano; Kazuki Takekawa; Hideaki Miyoshi; Yuhei Segawa; Keiichi Ito (Urology Video Journal)
Objective: Bulbar urethral necrosis is a rare and devastating complication of anastomotic urethroplasty for pelvic fracture urethral injury, which manifests as bulbar urethral loss due to inadequate retrograde blood supply after transection of the bulbar urethra. In this accompanying video, we demonstrate a case of bulbar urethral necrosis successfully salvaged using penile skin tube flap urethroplasty. Patient and surgical procedure: A 67-year-old male underwent anastomotic urethroplasty for a pelvic fracture urethral injury; however, he experienced urinary retention 3 months after urethroplasty. Urethrography revealed a long (40 mm) urethral defect, suggesting bulbar urethral necrosis. Salvage urethroplasty using a penile skin flap was performed 12 months after failure of the initial urethroplasty. A midline perineal incision was made and the necrotic bulbar urethral segment was excised entirely, exposing the healthy distal and proximal urethral ends. A transverse circular penile skin flap 3 cm wide was harvested and transposed to the perineum. Subsequently, a skin flap tube was created using a 5–0 polydioxanone running suture over a 14 Fr Foley catheter and was anastomosed to both urethral ends to fill the bulbar urethral defect. Results: The postoperative course was uneventful. Four weeks after salvage urethroplasty, the urethral catheter was removed and the patient resumed voiding. Postoperative cystourethroscopy revealed no recurrent stenosis and the flap was healthy with a wide urethral lumen. Two years after surgery, the patient continued to have a good voiding status. Conclusion: Penile skin tube flap urethroplasty may be a viable option for the repair of bulbar urethral necrosis.